The Effect of Informedness and Consensus on Price and Volume Behavior. - Holthausen, Robert W.; Verrecchia, Robert E. (The Accounting Review, 1990)
Abstract This paper presents a partially revealing rational expectations model of competitive trading to identify two effects of information releases; an informedness effect and a consensus effect. The informedness effect measures the extent to which agents become more knowledgeable, and the consensus effect measures the extent of agreement among agents at the time of an information release. We demonstrate that informedness and consensus generally occur jointly when information is disseminated, and that unexpected price changes and trading volume are each influenced by both informedness and consensus. Thus, interpretations of unexpected price changes and volume associated with information releases are conceptually similar. Since informedness and consensus each affect both the variance of price changes and volume, our paper provides an economic rationale for examining both price and volume effects at the time of information releases.